2011
DOI: 10.1002/adsc.201100572
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and Solvent‐Free Uncatalyzed Three‐Component Vinylogous Mukaiyama–Mannich Reactions of Pyrrole‐Based Silyl Dienolates

Abstract: A catalyst-free, environmentally benign three-component vinylogous Mukaiyama-Mannich reaction of pyrrole-based silyl dienolates is presented, which works effectively in both aqueous and solvent-free environments. Both lipophilic and hydrophilic aldehyde candidates are suitable substrates, allowing access to a rich repertoire of unsaturated vicinal aminolactam structures with virtually complete g-site selectivity and moderate to good anti-diastereoselectivity. The utility of this technology is highlighted by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 64 publications
0
9
0
2
Order By: Relevance
“…Along this line, Zanardi et al presented the first catalyst-free three-component vinylogous Mukaiyama–Mannich reaction (VMMnR) employing pyrrole silyl dienolates of type 842a , o -anisidine 869 , and diverse aldehydes 823 , which performed well in both aqueous and solvent-free environments ( Scheme 220 ). 576 Both lipophilic and hydrophilic, aromatic and aliphatic aldehydes proved to be competent substrates giving access to a wide collection of racemic α,β-unsaturated δ-aminolactams 870 in high isolated yields, with excellent levels of γ-site selectivity and chemoselectivity, and moderate to high diastereoselectivity in favor of anti -configured adducts. Of note, aqueous and solvent-free protocols were particularly suited for protected alkoxy aldehydes and highly hydrophilic substrates, leading to the corresponding adducts with promising yields and favorable anti -diastereoselectivity.…”
Section: Vinylogous Amides and Lactamsmentioning
confidence: 99%
“…Along this line, Zanardi et al presented the first catalyst-free three-component vinylogous Mukaiyama–Mannich reaction (VMMnR) employing pyrrole silyl dienolates of type 842a , o -anisidine 869 , and diverse aldehydes 823 , which performed well in both aqueous and solvent-free environments ( Scheme 220 ). 576 Both lipophilic and hydrophilic, aromatic and aliphatic aldehydes proved to be competent substrates giving access to a wide collection of racemic α,β-unsaturated δ-aminolactams 870 in high isolated yields, with excellent levels of γ-site selectivity and chemoselectivity, and moderate to high diastereoselectivity in favor of anti -configured adducts. Of note, aqueous and solvent-free protocols were particularly suited for protected alkoxy aldehydes and highly hydrophilic substrates, leading to the corresponding adducts with promising yields and favorable anti -diastereoselectivity.…”
Section: Vinylogous Amides and Lactamsmentioning
confidence: 99%
“…Focusing better on the initial VMMnR operation, it was previously reported that mixing pyrrole-derived silyloxy diene 7, 14 D-mannitol-derived glyceraldehyde 8 and commercial o-anisidine 9 under neat or on-water conditions at 30 °C under ultrasonic irradiation produced the expected vinylogous Mannich product in a high global yield (neat, 96% yield; onwater, 95% yield) as a mixture of three separable diastereoisomers, namely (3S,4S,5S)-configured 10a (target numbering, 42%), (3S,4R,5R)-isomer 10b (34-39%), and (3S,4R,5S)-isomer 10c (15-20%) (Scheme 2). 15 Parallel application of the designed general plan to each individual isomer 10a, 10b, 10c, plus 10d, derived from 10a by base-promoted C5-epimerization, would in principle deliver 4-epi-oseltamivir, 5-epi-oseltamivir, oseltamivir itself, and 4,5di-epi-oseltamivir, respectively. By including stereoisomers obtained from L-glyceraldehyde precursor ent-8, the execution of the whole plan would ultimately lead to all eight possible stereoisomers of the oseltamivir core.…”
Section: Synthesis Planningmentioning
confidence: 99%
“…[5] Over the years, there have been additional advances,i ncluding the development of cascade reactions, [6] vinylogous variants, [7] and onwater protocols. [8] Despite these advances,o ne fundamental piece of the puzzle was still missing:the efficient and truly general use of the smallest enolizable aldehyde,a cetaldehyde.T he use of this substrate was frustrated by seemingly unsolvable issues, in particular,t he inability of the small acetaldehyde SEE to discriminate between the starting aldehyde acceptor and the product aldehyde,t hus leading to extensive polymerization. Thef irst encouraging results from attempts to address this issue were obtained by Yamamoto and co-workers in 2006, [9] who were first to recognize that an extremely bulky tris-(trimethylsilyl) SEE ("super-silyl") of acetaldehyde could be employed to develop asuccessful catalytic (although racemic) MAR.…”
mentioning
confidence: 99%